Inferior alveolar neurovascular bundle repositioning: a retrospective analysis. Issue 4 (April 2017) - Sethi, A.; Banerji, S.; Kaus, T.
Abstract: In this study, patients with an insufficient height of bone for implant placement in the posterior mandible were treated by repositioning of the inferior alveolar neurovascular bundle (IANVB). These patients were divided into two groups: those in group A ( n  = 69) did not require a bone graft and implants were placed at the time of nerve repositioning; those in group B ( n  = 9) received bone grafts in conjunction with nerve repositioning and implants were placed upon maturation of the grafts. One hundred and twenty-one nerves were repositioned in 78 patients and 308 implants were placed. Three implants failed within the first 10 months after placement. With a certainty of 95%, an estimated overall mean survival rate better than 97.8% was observed after a mean observation period of 84.5 months. The recovery of sensation was monitored using standardized tests. The recovery of sensation varied from 24 h to 6 months. Five patients reported some residual altered sensation. The technique of repositioning the IANVB provides an effective way of treating the atrophic posterior mandible with acceptable morbidity and a high implant survival rate; however the risk of dysesthesia must be acknowledged and patients properly informed.